The Determination of Molecular and Toxicological Mechanisms of Cucurbitacin E in Model Organism Drosophila melanogaster and Various Cancer Cell Lines: Molecular Modelling, Docking and Dynamic Simulation Studies. - Tunçbilek, A.; Azarkan, S.Y.; Ercan, F. (Current computer-aided drug design, 2023)
Cucurbitacins are one of the most important components of Ecballium elaterium. Among the cucurbitacins, Cucurbitacin E was the first to be isolated. This study focused on screening the anticancer and insecticidal potential of Cucurbitacin E by the in-vitro, invivo, and in-silico methods. In the study, toxicity analysis of Cucurbitacin E was determined on HeLa, Caco 2 cancer cell lines and D. melanogaster. While the expression levels of the BAD, BCL-2, AKT-1 and H-purine genes of cancer cell lines were determined, the CG15530, BUFFY, AKT-1 and Purine genes of D. melanogaster were determined by RT-PCR. Besides, molecular docking and dynamic properties of Cucurbitacin E with human and insectoid enzymes were presented in silico. The IC50 value of Cucurbitacin E in the HeLa ovarian and Caco 2 colon cancer cell lines was determined to be 42 ug/ml and 85 ug/ml, respectively. The LC50 and LC99 doses for fruit flies were determined to be 47,693 μg/ml and 133,251 μg/ml, respectively. Gene expression analysis revealed that Cucurbitacin E showed the greatest effect on Purine and AKT-1 genes in D. melanogaster. We analyzed all genes by Western blot but did not detect significant changes in genes other than H-purine. In silico studies revealed that the Purine protein of D. melanogaster had the highest bonding energy with Cucurbitacin E as a ligand. Similarly, Cucurbitacin E showed great affinity towards H-purine (-10.2 kcal/mol). Molecular dynamics simulation studies were also performed to determine the stability of the dynamic process. As a result of our in vivo, in vitro and bioinformatic analyzes, it has been seen that Cucurbitacin E is effective against the cancer types and model insects studied.